Synthesis of V-doped In2O3 Nanocrystals via Digestive-Ripening Process and Their Electrocatalytic Properties in CO2 Reduction Reaction - Kim, Myeong-Geun; Jeong, Jinhoo; Choi, Youngjo; Park, Jinwoo; Park, Eunjoon; Cheon, Cheol-Hong; Kim, Nak-Kyoon; Min, Byoung Koun; Kim, Woong (American Chemical Society, 2020)
The development of synthetic methods for monodisperse nanomaterial is of great importance in science and technology related to nanomaterials. The strong demands to prepare exceptionally monodisperse nanocrystals have made digestive-ripening one of the most sought-after size-focusing processes. Although digestive-ripening processes have been demonstrated to produce various metals and semiconductors, their applicability to oxides has rarely been studied despite various unique properties and applications of oxide nanomaterials. In this work, we demonstrate the successful synthesis of monodisperse V-doped In2O3 nanocrystals via a modified digestive-ripening process. The nanocrystals have truncated octahedral shape faceted with eight (222) and six (220) planes. To the best of our knowledge, this is the first report on the digestive-ripening synthesis of highly symmetrical doped oxide nanocrystals. Moreover, V-doped In2O3 nanocrystals exhibit electrocatalytic activities for CO2 electrochemical reduction and produce CH3OH, which has not been attainable from previously reported electrocatalysts based on indium or indium oxide. This distinctive catalytic property of V-doped In2O3 is attributed to the presence of V-dopants in the In2O3 host. Our demonstration has important implications for both nanocrystal synthesis and electrocatalyst development.